Deconstructing Concealed Gayness Text in The Film Negeri van Oranje: Critical Discourse Analysis - Heri Setiawan (Humaniora, 2018)
As one of the most popular creative cultural products, film sometimes speaks beyond what it presents. It is not always produced merely for entertainment purposes, but also to spread a certain ideology and represent a particular culture. Anchored in queer theory, this research looks at the Indonesian film, Negeri Van Oranje, which was chosen purposely to be analyzed using Fairclough’s critical discourse analysis model with an aim to deconstruct the concealed gayness text in the film. From the analysis, it was found that the gay scenes in the film try to tell its audience about the positions, feelings, challenges, and rejections that Indonesian gay people experience living amongst heteronormative surroundings. Some new notions about gay people’s life in Indonesia are extracted based on the analysis of the gay scenes in the film. The strategy of inserting gay content into a film nationally released in Indonesia is also revealed. The results of the analysis could be used to create a picture of what gay life looks like in Indonesia, a multicultural country that is well-known as the place in which the world’s largest Muslim population dwells.